Avaliação de resistência mecânica e análise de forma geométrica de elementos de fixação por rosca fabricados através de manufatura aditiva - Prado, Thiago Menezes do (2023)
The work addresses the mechanical tensile strength of internal fillets in specimens manufactured in PLA and ABS from additive manufacturing by Fused Deposition Modelling (FDM). Test specimens measuring 30 x 30 x 20 mm were manufactured in PLA and ABS with a 3D printer model Ender 3 V2. The through hole of the specimens has measurements M12 x 1.75. Varied parameters used were: infill (p), number of walls (w) and height of the layers (h), to enable the understanding of how the mechanical resistance of the material is affected. Thus, the present study aimed to compare the mechanical resistance of PLA and ABS polymers through tensile tests, defining which material has greater resistance and with low production cost from 3D printing. The tensile tests were carried out using a tensile machine with a maximum capacity of 600 kN, which gradually applied tension to the specimens until the material fractured or ruptured. For the result analysis, relation of resistance from the specimens was verified graphically (force x time) and statistically (ANOVA), judging the influence of variables in individual and collective content in the achieved results. Pieces printed in PLA showed a higher quality of mechanical resistance compared to those made from ABS material when graphic results obtained were verified. As a statistical result, the ANOVA analysis identified the factor with greatest influence on tests were infill (P%), being preponderant both individually and collectively, when analyzing its influence with other two variables.